The Price of Corruption on State Losses Policy - Rahmadi, Aji; Karjoko, Lego; Hartiwiningsih, Hartiwiningsih (Volksgeist: Jurnal Ilmu Hukum dan Konstitusi, 2025)
Legal instruments and law enforcement agencies have actively pursued efforts to eradicate corruption; however, empirical evidence indicates that the recovery of state financial losses remains disproportionate to the magnitude of economic harm incurred. This study seeks to reformulate the concept of state economic loss in corruption cases to establish a legal framework that is fairer, proportionate, and grounded in legal certainty. The research uses a normative juridical method, analyzing secondary data through three distinct approaches: the statutory approach, which examines the consistency of legal norms; the conceptual approach, which investigates relevant doctrines and theoretical frameworks; and the case study approach, which identifies judicial practices and jurisprudence relevant to the topic. The findings reveal two principal insights. First, the application of the economic loss element in state corruption cases encounters significant challenges, including ambiguous interpretations, the absence of clear normative boundaries, reliance on potential rather than actual loss calculations, and the lack of a standardized methodology. Second, reformulating this element is necessary by clarifying its normative definition, incorporating actual losses, recognizing systemic impacts, and standardizing the methodology for calculating losses. This reformulation enhances the quality of evidence, reduces disparities in legal interpretation, and promotes harmonization across laws and regulations. Moreover, this policy framework is expected to improve coordination among law enforcement agencies, strengthen public trust, and ultimately foster a more effective, transparent, and corruption-free governance environment.